PENGEMBANGAN BAHAN AJAR MENGANALISIS UNSUR PEMBANGUN CERPEN BERDASARKAN KAJIAN STRUKTURAL DI SMA NEGERI 5 SAMARINDA - Wasis Sirutama; Syaiful Arifin; Bibit Suhatmady; Muhammad Bahri Arifin; Widyatmike Gede Mulawarman; Masrur Yahya (Media Bina Ilmiah, 2025)
Teacher's book is a document that serves as a guideline for teachers during the implementation of learning and student books that serve as references. There is only a little literature on short story structure. In short story material for Senior High Schools (SMA), it is necessary to utilize teaching materials needed by teachers. In the structural study of Robert Stanton's literary work, there are facts and story tools that help in analyzing the elements of short story builders in SMA. The researcher chose the short story Summa Cum Laude by Syafruddin Pernyata because he is an East Kalimantan writer who is known as a literary figure and is active in the literacy movement. Research related to short stories is very necessary to be studied because it is important for teachers or readers to understand the basics of short story content which has many benefits in relation to literary learning. Therefore, this study was conducted to answer: (1) Develop teaching materials to analyze short story building elements based on structural studies for class XI students of SMA Negeri 5 Samarinda. (2) Describe the effectiveness of teaching materials to analyze short story building elements based on structural studies and for class XI students of SMA Negeri 5 Samarinda. This study uses the R&D method or (Research and Development). In this study, the ADDIE development model was used. Research and Development Results: A. The development flow consists of (1) Collecting and creating materials consisting of analyzing the elements of short story builders based on structural studies and revealing moral values in short story texts. (2) Design of teaching materials in the form of printed physical books. (3) The results of validation by material experts who have a percentage of 87.5% with a very feasible category, design experts who have a percentage of 100% with a very feasible category, and language experts who have a percentage of 97% with a very feasible category. B. The results of developing teaching materials analyzing the elements of short story builders consist of (1) Small group tests consisting of a pretest with an average score of 50.9 and a posttest with an average score of 87.1. (2) Trials in large groups consisting of a pretest with an average score of 73.2 and a posttest with an average score of 86.55. (3) Assessment of student respondents consisting of small and large groups and researchers conducting interviews. (C) The effectiveness of the use of teaching materials is an increase in student scores above the KKM score and the N-Gain (g) test analysis obtained medium and high categories.. (10pt).